An evaluation of an educational intervention to reduce inappropriate cannulation and improve cannulation technique by paramedics. Issue 11 (22nd October 2009) - Siriwardena, A N; Iqbal, M; Banerjee, S; Spaight, A; Stephenson, J
Abstract : Background: Intravenous cannulation enables administration of fluids or drugs by paramedics in prehospital settings. Inappropriate use and poor technique carry risks for patients, including pain and infection. We aimed to investigate the effect of an educational intervention designed to reduce the rate of inappropriate cannulation and to improve cannulation technique. Method: We used a non-randomised control group design, comparing two counties in the East Midlands (UK) as intervention and control areas. The educational intervention was based on Joint Royal Colleges Ambulance Liaison Committee guidance and delivered to paramedic team leaders who cascaded it to their teams. We analysed rates of inappropriate cannulation before and after the intervention using routine clinical data. We also assessed overall cannulation rates before and after the intervention. A sample of paramedics was assessed post-intervention on cannulation technique with a "model" arm using a predesigned checklist. Results: There was a non-significant reduction in inappropriate (no intravenous fluids or drugs given) cannulation rates in the intervention area (1.0% to 0%) compared with the control area (2.5% to 2.6%). There was a significant (p<0.001) reduction in cannulation rates in the intervention area (9.1% to 6.5%; OR 0.7, 95% CI 0.48 to 1.03) compared with an increase in the control area (13.8% to 19.1%; OR 1.47, 95% CI 1.15 to 1.90), a significant difference (p<0.001). Paramedics in the intervention area were significantly more likely to use correct hand-washing techniques post-intervention (74.5% vs. 14.9%; p<0.001). Conclusion: The educational intervention was effective in bringing about changes leading to enhanced quality and safety in some aspects of prehospital cannulation.